1989
DOI: 10.1016/s0022-5347(17)40715-4
|View full text |Cite
|
Sign up to set email alerts
|

The Enigma of Non-Gonococcal Urethritis: Role for Bacteroides Ureolyticus

Abstract: SUMMARY Although up to about halfthe cases ofacute non-gonococcal urethritis (NGU) are caused by Chlamydia trachomatis organisms (chlamydiae) and a smaller, ill-defined, proportion probably by Ureaplasma urealyticum organisms (ureaplasmas), the aetiology of all cases is not understood. Clarification of the role of the anaerobe, Bacteroides ureolyticus, was sought in the current study. Seventy five chlamydia negative patients with NGU were treated on a double blind placebo controlled basis with metronidazole. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…B. ureolyticus is, considered to be part of the normal¯ora in both the male and female genital tract, has also been isolated from mixed cultures of infections of virtually every organ system in man (Duerden et al, 1982). It has previously been found to be associated with male nongonococcal urethritis, where it was suggested that this organism may have a pathogenic role (Hawkins et al, 1988;Balmelli et al, 1994). Eley et al (1995) studied the pathogenicity of B. ureolyticus in animals and established that a pure culture of B. ureolyticus is capable of producing infection when it is injected subcutaneously into mice.…”
Section: Discussionmentioning
confidence: 99%
“…B. ureolyticus is, considered to be part of the normal¯ora in both the male and female genital tract, has also been isolated from mixed cultures of infections of virtually every organ system in man (Duerden et al, 1982). It has previously been found to be associated with male nongonococcal urethritis, where it was suggested that this organism may have a pathogenic role (Hawkins et al, 1988;Balmelli et al, 1994). Eley et al (1995) studied the pathogenicity of B. ureolyticus in animals and established that a pure culture of B. ureolyticus is capable of producing infection when it is injected subcutaneously into mice.…”
Section: Discussionmentioning
confidence: 99%
“…B. ureolyticus is, considered to be part of the normal flora in both the male and female genital tract, has also been isolated from mixed cultures of infections of virtually every organ system in man (Duerden et al ., 1982). It has previously been found to be associated with male non‐gonococcal urethritis, where it was suggested that this organism may have a pathogenic role (Hawkins et al ., 1988; Balmelli et al ., 1994). Eley et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only six (23%) of 26 anaerobe negative men responded to metronidazole therapy. 18 However, other workers have isolated B ureolyticus as frequently from men with NGU as from those without NGU and contend that this organism is merely a part of the normal urethral flora. '9 G vaginalis has been isolated from the urethra of 11.4% of male GUM attendees and more often from heterosexual than homosexual individuals.20 Its presence, however, was not associated with symptoms of urethritis, although microscopic evidence of inflammation was not sought.…”
Section: Discussionmentioning
confidence: 99%